Phonological Process in Passive Verb Markers of Bahasa Bakumpai - Yusuf Al Arief (Master Program in Linguistics, Diponegoro University, 2019)
This research is about the phonological process which occurs in the forming of passive verbs in bahasa Bakumpai. The theory applied in this research is generative phonology. The object of this research is bahasa Bakumpai, one of the languages used by people in South and Central Borneo who live by Barito River. The research was conducted with descriptive qualitative method. The data collection was conducted by searching active and passive verbs in bahasa Bakumpai dictionary and verified by a native speaker. Result of the research shows that the prefix which becomes the passive marker is /i/ and when it is attached to stems begin with consonants, there are insertions of consonants such as the [n], [m], [ng], and [ny] which are categorized as allophones since they occur in complementary distribution in the environments.